KEY ASPECTS OF MODERN ANTI-CRISIS CONSULTING - Vasilchuk, O.I; Schneider, V.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The article identifies relevant aspects of crisis management consulting, indicating a lack of sophistication of this issue at the present time. The disclosure of aspects of crisis management consulting and the context of its optimal use gives an understanding of the positive role that this process can play in strengthening the financial and economic mechanism of organizations. Currently, more and more organizations in the system of market relations are faced with problems. And increasingly, there is a situation when organizations cannot solve the problem on their own. Organizations are forced to turn to outside organizations for help. These are organizations providing consulting services, and one of these is crisis management consulting. Diagnosis of the economic condition and solving the crisis state of the enterprise is a large-scale task requiring large resources and highly qualified personnel, which most organizations do not have, but have an anti-crisis consultant. New challenges and challenges for organizations are posed by a dynamic, modern world. It is obvious that the world economy is currently changing dynamically and companies that are not able to respond to changes and do not adapt under the pressure of new conditions dictated by the market cease to exist.